2023
DOI: 10.1039/d3se00227f
|View full text |Cite
|
Sign up to set email alerts
|

Operando FTIR study of the photocatalytic reduction of CO2 in the presence of water vapor over Pt/TiO2: on the role of surface residual C-species

Abstract: Benchmark TiO2 and Pt/TiO2 photocatalysts were investigated by operando FTIR spectroscopy to shed light on catalytic pathways influencing CO2 photoreduction in vapor phase. Through combination with multivariate curve resolution-chemometric analysis,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…S4†) are chemically reactive and capable of being readily converted into intermediates/products under irradiation as reported in our previous study. 5…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S4†) are chemically reactive and capable of being readily converted into intermediates/products under irradiation as reported in our previous study. 5…”
Section: Resultsmentioning
confidence: 99%
“…2 Moreover, recent studies have also evidenced the formation of C2 products through C–C coupling mechanisms, such as ethane (C 2 H 6 ), ethanol (C 2 H 5 OH), ethylene (C 2 H 4 ) and acetic acid (CH 3 COOH). 3–5…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 These residues, originating from catalyst preparation or organic compound adsorption, can contribute to reaction products, complicating the attribution of products solely to CO 2 reduction. 13 Our previous study demonstrated that carbon residues significantly impact CO 2 photocatalytic reduction, accounting for up to 40% of methane yields. 14 Given the low yields of CO 2 conversion, it is crucial to distinguish between products from residual-carbon impurities and those from the reduction of CO 2 to better understand the underlying reaction mechanisms.…”
Section: ■ Introductionmentioning
confidence: 99%